2015
DOI: 10.1002/prot.24955
|View full text |Cite
|
Sign up to set email alerts
|

Toward rational thermostabilization of Aspergillus oryzae cutinase: Insights into catalytic and structural stability

Abstract: Cutinases are powerful hydrolases that can cleave ester bonds of polyesters such as poly(ethyleneterephthalate) (PET), opening up new options for enzymatic routes for polymer recycling and surface modification reactions. Cutinase from Apsergillus oryzae (AoC) is promising owing to the presence of an extended groove near the catalytic triad which is important for the orientation of polymeric chains. However, the catalytic efficiency of AoC on rigid polymers like PET is limited by its low thermostability; as it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…Generally, the structural information of these Thermobifida cutinases was important in engineering towards improved thermostability (Then et al, ; Thumarat et al, ). In addition to Thermobifida cutinases, the structural basis for thermostability of other cutinases like from another compost organisms, namely Saccharomonospora viridis or from Aspergillus oryzae was recently discussed (Miyakawa et al, ; Shirke et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the structural information of these Thermobifida cutinases was important in engineering towards improved thermostability (Then et al, ; Thumarat et al, ). In addition to Thermobifida cutinases, the structural basis for thermostability of other cutinases like from another compost organisms, namely Saccharomonospora viridis or from Aspergillus oryzae was recently discussed (Miyakawa et al, ; Shirke et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the potential of these enzymes, especially processing of cheap bulk polymers will require more efficient enzymes. Recently, various strategies for the improvement of such enzymes hydrolysing polyethylene terephthalate (PET) related to thermostability (Miyakawa et al, ; Shirke et al, ; Then et al, ), ultrasound activation (Pellis et al, ), and active site architecture (Araujo et al, ; Silva et al, ; Wei et al, ) were reported. In addition, we have demonstrated that the attachment of hydrophobic binding modules (Gamerith et al, ; Ribitsch et al, ) or hydrophobins to cutinases (Ribitsch et al, ) or enzyme surface engineering (Herrero Acero et al, ) can tune sorption properties and thereby improve PET hydrolysis .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it suggests that efficient enzymatic degradation of PET requires thermostable PET depolymerases. Approaches of glycosylation (Shirke et al, 2018) and rational protein engineering, such as the optimization of surface salt bridge (Shirke et al, 2016), mutation of Ca 2+ and Mg 2+ binding sites , introduction of disulfide bridge , stabilization of a β6-β7 connecting loop, and extension of subsite IIc (Son et al, 2019), have been applied to improve the thermostability of these PET hydrolases. Notwithstanding, there is room for increasing the half-life of PET hydrolases above 65 • C.…”
Section: Petmentioning
confidence: 99%
“…However, most variants lost their activity at temperatures well below the thermal unfolding temperature, due to an earlier active site denaturation. Consequently, further research has to be performed in order to design thermostable variants that maintain their activities at elevated temperatures [61].…”
Section: Structural Determinants Of Cutinase Stabilitymentioning
confidence: 99%